2011
DOI: 10.1155/2011/981214
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota and Human Health with an Emphasis on the Use of Microencapsulated Bacterial Cells

Abstract: The gut microbiota plays a crucial role in maintaining health. Alterations of the gut bacterial population have been associated with a number of diseases. Past and recent studies suggest that one can positively modify the contents of the gut microbiota by introducing prebiotics, probiotics, synbiotics, and other therapeutics. This paper focuses on probiotic modulation of the gut microbiota by their delivery to the lower gastrointestinal tract (GIT). There are numerous obstacles to overcome before micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 120 publications
1
80
0
8
Order By: Relevance
“…Insulin-deprived T1DM and T2DM patients exhibited elevated levels of hippurate, dimethylamine or trimethylamine-N-oxide (Messana et al 1998, Zuppi et al 2002, although a separate study observed lower levels of hippurate and 3-hydroxyhippurate among pre-diabetic individuals with impaired glucose tolerance (Zhao et al 2010b). The human gut microbiota has an important role in health, which has been comprehensively discussed by several authors (Nicholson et al 2005, Fujimura et al 2010, Prakash et al 2011 and is outside the focus of the present review.…”
Section: Patient Investigationsmentioning
confidence: 91%
“…Insulin-deprived T1DM and T2DM patients exhibited elevated levels of hippurate, dimethylamine or trimethylamine-N-oxide (Messana et al 1998, Zuppi et al 2002, although a separate study observed lower levels of hippurate and 3-hydroxyhippurate among pre-diabetic individuals with impaired glucose tolerance (Zhao et al 2010b). The human gut microbiota has an important role in health, which has been comprehensively discussed by several authors (Nicholson et al 2005, Fujimura et al 2010, Prakash et al 2011 and is outside the focus of the present review.…”
Section: Patient Investigationsmentioning
confidence: 91%
“…Probiotics are dietary supplements containing bacteria which, when administered in adequate amounts, confer a health benefit on the host [14,20]. Probiotics, as natural compounds, are generally considered safe, but can also be tested for set-out safety parameters [21].…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics, as natural compounds, are generally considered safe, but can also be tested for set-out safety parameters [21]. A number of studies have investigated bacterial strains for a range of conditions, including infections, allergies and metabolic disorders such as ulcerative colitis and Crohn's disease [14]. Promising research focuses on the microbial secretion and production of beneficial biologically active enzymes and proteins, including: ornithine decarboxylase for the treatment of autoimmune diseases and accelerated cell apoptosis [22], bile salt hydrolase for hypercholesterolemia [23;24], and bile transport and tolerance proteins for the efficient delivery of probiotics [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations